WANPRESTASI NASABAH KREDIT USAHA RAKYAT PADA UNIT USAHA MIKRO BANK KALBAR CABANG PONTIANAK - NIM. A1012151083, MEFI FAHRIA UTAMI (Fakultas Hukum Universitas Tanjungpura, 2022)
ABSTRACT This thesis is entitled Default of People's Business Credit Customers at the Micro Business Unit of Bank Kalbar. Bank is one of the financial institutions or companies engaged in finance. The definition of a bank is a business entity that collects funds from the public in the form of savings and distributes them back to the community in the form of credit and or other forms in order to improve the standard of living of the people at large. Meanwhile, the banking business includes three activities, namely collecting funds, distributing funds, and providing other bank services. The activity of collecting and distributing funds is the main activity of the bank, while providing other bank services is only a supporting activity. Activities to raise funds, in the form of collecting funds from the public in the form of demand deposits, savings, and time deposits. The problem of this research is